人Notch-1基因RNA干扰慢病毒载体的构建及鉴定 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: To construct and identify a lentiviral vector of RNA interference targeting human Notch-1 gene. METHODS: To determine the Notch-1 gene sequences, three RNAi target sequences (shRNA1-3) were designed in accordance with the RNAi sequence design principles and cloned into the lentiviral vector pLenOR-THM by endonuclease BamH I restriction, EcoR I double digestion, and T4 DNA-ligase ligation. After the transformation into competent DH5α bacteria, the candidate clones were identified by Kpn I and EcoR I double digestion and DNA sequencing. The recombinant and three packaging plasmids were co-transfected into human embryonic kidney cell line 293T cells by lipofectamine to produce the lentiviral particles. The viral titer was determined. The 293T cells were infected by the lentiviral particles obtained, and transfection efficiency was assessed using a fluorescent microscope. The lentiviral vector particles were also transfected into ACC-M cells. The Notch-1 expression in the transfected cells was assayed by quantitative reverse transcription polymerase chain reaction (QRT-PCR) and Western blot analysis. RESULTS: The lentiviral RNAi vector pLenOR-THM-Notch1 for Notch-1 gene was constructed successfully. Strong green fluorescence was observed in the 293T cells under fluorescent microscope after co-transfection of the cells with the four plasmids of lentiviral vector. The virus in the supernatant reached a titer of 5.8×10(8) TU·mL(−1). The transfection efficiency of the collected virus exceeded 90% in 293T cells with 1 as a multiplicity of infection. The third lentiviral vector was found to significantly inhibit the Notch-1 expression at the mRNA and protein levels. CONCLUSION: The lentiviral RNAi vector of Notch-1 has been successfully constructed and identified.